Anticancer Activity of Reconstituted Ribonuclease S‐Decorated Artificial Viral Capsid. (21st June 2022) - Liang, Yingbing; Furukawa, Hiroto; Sakamoto, Kentarou; Inaba, Hiroshi; Matsuura, Kazunori
Abstract: Ribonuclease S (RNase S) is an enzyme that exhibits anticancer activity by degrading RNAs within cancer cells; however, the cellular uptake efficiency is low due to its small molecular size. Here we generated RNase S‐decorated artificial viral capsids with a size of 70–170 nm by self‐assembly of the β ‐annulus‐S‐peptide followed by reconstitution with S‐protein at neutral pH. The RNase S‐decorated artificial viral capsids are efficiently taken up by HepG2 cells and exhibit higher RNA degradation activity in cells compared with RNase S alone. Cell viability assays revealed that RNase S‐decorated capsids have high anticancer activity comparable to that of standard anticancer drugs. Abstract : RNase S‐decorated artificial viral capsid that exhibited enzyme activity were constructed by reconstituting β ‐annulus‐S‐peptide with S‐protein at neutral pH. The RNase S‐decorated capsids taken up by HepG2 cells exhibited higher RNA degradation and anticancer activity in cells compared with RNase S alone.